Conceptual issues related to the construction of prescriptive standards for the evaluation of postnatal growth of preterm infants. Issue 12 (6th April 2010) - Villar, J; Knight, H E; de Onis, M; Bertino, E; Gilli, G; Papageorghiou, A T; Ismail, L Cheikh; Barros, F C; Bhutta, Z A
Abstract : Monitoring and interpreting the growth of preterm infants is a major clinical task for neonatologists. The effectiveness of this process depends upon the robustness of the standard selected. Concerns have been raised regarding the nature of the charts currently being used, as well as their appropriateness for present-day neonatal care. To overcome these problems, there is a need for new prescriptive standards based on a population of preterm infants without evidence of impaired fetal growth and born to low-risk women followed up since early pregnancy for precise gestational age dating. Preterm infants contributing to the new standards should be free of congenital malformations and major clinical conditions associated with impaired postnatal growth. These infants should receive standardised, evidence-based clinical care and should follow current feeding recommendations based on exclusive/predominant breastfeeding. This strategy should provide a population that is conceptually as close as possible to the prescriptive approach used for the construction of the WHO infant and child growth standards. New international standards constructed in this way should contribute to the evidence-based care of these preterm infants.